Cyclic Bicytopenia in a Patient with Shapiro Syndrome - Lindsey E. Roeker; Vinay Gupta; Wilson I. Gonsalves; Alexandra P. Wolanskyj; Naseema Gangat (Case Reports in Hematology)
Shapiro syndrome and periodic hypothermia have been reported approximately fifty times in the literature. Shapiro syndrome is defined as the constellation of periodic hypothermia and hyperhidrosis along with agenesis of the corpus callosum by Shapiro et al. in 1969. Periodic hypothermia is a more broad diagnosis with a number of proposed mechanisms; it occurs in patients without structural brain abnormalities. Hematologic abnormalities beyond iron-deficiency anemia have not been documented in any of the reported cases of Shapiro syndrome or periodic hypothermia. Though accidental and therapeutic hypothermia have been associated with thrombocytopenia, this is, to our knowledge, the first reported case of periodic intrinsic hypothermia causing bicytopenia. In this report, we present the case of a patient with Shapiro syndrome who experienced cyclic bicytopenia mirroring hypothermic episodes. We address the differential diagnosis of bicytopenia, review the mechanisms proposed for cytopenias related to hypothermia, and propose possible mechanisms for the finding in this case.